2016
DOI: 10.1007/s13592-016-0440-z
|View full text |Cite
|
Sign up to set email alerts
|

Risk indicators affecting honeybee colony survival in Europe: one year of surveillance

Abstract: -The first pan-European harmonized active epidemiological surveillance program on honeybee colony mortality (EPILOBEE) was set up across 17 European Member States to estimate honeybee colony mortality over winter and during the beekeeping season. In nine Member States, overwinter losses were higher and statistically different from the empirical level of 10 % under which the level of overwinter mortality was considered as acceptable with usual beekeeping conditions. In four other countries, these losses were lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
59
0
8

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 69 publications
(75 citation statements)
references
References 21 publications
8
59
0
8
Order By: Relevance
“…The statistical analysis of our data from the first year has shown that size of the operation, apiary and the clinical disease (varroosis, AFB and nosemosis) observed during the previous autumn were significant risk indicators of overwinter honey bee colony survival [20]. In the present study, our findings find a similar result when considering two study years.…”
Section: Discussionsupporting
confidence: 83%
“…The statistical analysis of our data from the first year has shown that size of the operation, apiary and the clinical disease (varroosis, AFB and nosemosis) observed during the previous autumn were significant risk indicators of overwinter honey bee colony survival [20]. In the present study, our findings find a similar result when considering two study years.…”
Section: Discussionsupporting
confidence: 83%
“…Тривають дискусії щодо впливу на здоров`я та життєдіяльність бджіл низки різноманітних факторів: застосування пестицидів (зокрема, неонікотиноїдів), зменшення різноманіття квіткових рослин, поширення хвороб та паразитів, вирощування генетично модифікованих культур, електромагнітне випромінювання, забруднення води, повітря та ґрунтів та ін. (Chauzat et al, 2016;Genersch et al, 2010;Godfray, 2014). Україна характеризується вдалим поєднанням комплексу факторів, що створюють передумову до зростання кількості колоній Apis mellifera L. (сприятливий помірний клімат, порівняно великі площі непосівних земель, а також значні площі земель, зайняті під вирощування соняшнику, з якого отримують популярний тип меду).…”
Section: моніторинг втрат колоній медоносних бджілunclassified
“…(COLOSS…, 2017;Brodschneider et al, 2016). Цієї зими всеєвропейська програма нагляду, що проводилась в 17 країнах, констатувала зимову смертність на основі польових досліджень в діапазоні від 4,7% до 30,6% в різних країнах (Chauzat et al, 2016). Встановлено, що клінічно виявлені захворювання (варроатоз, американський гнилець і нозематоз) перед заходом колоній в зиму вносять значний внесок в зимову смертність.…”
Section: результати досліджень та їх обговоренняunclassified
See 2 more Smart Citations